Hydrological Connectivity and Local Environment Alternately Drive Spatial Structure of Floodplain Aquatic Community Across Seasons - Hiromi Uno; Shunsuke Utsumi; Kentaro Morita; Osamu Kishida; Md. Khorshed Alam; Junjiro Negishi (Ecology and Evolution, 2025)
ABSTRACT Seasonal changes in the environment often strongly influence biological communities. In environmental transition zones, or ecotones, the environment fluctuates over time between two different types of environments and the seasonal change is more pronounced. Although emphasis has been placed on the spatial variation of biota along environmental gradients, seasonal change has not been well studied despite the seasonal nature of many ecotones. In this study, we investigated seasonal shifts in aquatic community structures of floodplain waterbodies characterised as transitions between lotic and lentic environments, and further investigated the biological processes behind the shift. We observed a clear seasonal shift of community structure in floodplain waterbodies. From the spring snowmelt season to the summer low flow season, the aquatic community structure was largely driven by the hydrological connectivity to the river, represented as the timing of the lotic–lentic transition during the seasonal flood recession. In contrast, after a few months of summer low flow period, the effect weakened over time, and the communities were structured based more on the basis of the local environment. The seasonal shift was largely explained by the change in amphibian and aquatic insect larvae, the main members of the floodplain aquatic assemblage, which metamorphose and emerge from the water during the summer period and then redistribute in different ways more strongly influenced by local environmental factors such as water body size, temperature and dissolved oxygen levels. Given that biota in ecotones occupy the habitat for a limited time due to the severe environmental fluctuations, such seasonal changes as we observed in this study may be widespread in ecotones. Landscape and local environmental conditions could alternately shape community structures in different seasons. Further attention to the temporal aspects of community structure is needed for community studies and for conservation.